High levels of B-type natriuretic peptide predict weaning failure from mechanical ventilation in adult patients after cardiac surgery - Lara, Thiago Martins (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2013)
OBJECTIVE: The failure to wean from mechanical ventilation is related to worse outcomes after cardiac surgery. The aim of this study was to evaluate whether the serum level of B-type natriuretic peptide is a predictor of weaning failure from mechanical ventilation after cardiac surgery. METHODS: We conducted a prospective, observational cohort study of 101 patients who underwent on-pump coronary artery bypass grafting. B-type natriuretic peptide was measured postoperatively after intensive care unit admission and at the end of a 60-min spontaneous breathing test. The demographic data, hemodynamic and respiratory parameters, fluid balance, need for vasopressor or inotropic support, and length of the intensive care unit and hospital stays were recorded. Weaning failure was considered as either the inability to sustain spontaneous breathing after 60 min or the need for reintubation within 48 h. RESULTS: Of the 101 patients studied, 12 patients failed the weaning trial. There were no differences between the groups in the baseline or intraoperative characteristics, including left ventricular function, EuroSCORE and lengths of the cardiac procedure and cardiopulmonary bypass. The B-type natriuretic peptide levels were significantly higher at intensive care unit admission and at the end of the breathing test in the patients with weaning failure compared with the patients who were successfully weaned. In a multivariate model, a high B-type natriuretic peptide level at the end of a spontaneous breathing trial was the only independent predictor of weaning failure from mechanical ventilation. CONCLUSIONS: A high B-type natriuretic peptide level is a predictive factor for the failure to wean from mechanical ventilation after cardiac surgery. These findings suggest that optimizing ventricular function should be a goal during the perioperative period.